2017
DOI: 10.3991/ijim.v11i6.6379
|View full text |Cite
|
Sign up to set email alerts
|

A Methodology to Develop a Mobile Application Model to Appraise Housing Design Quality

Abstract: Abstract-The variety of planning and design solutions occasionally turns into an underpinning factor for the defects and maintenance issues in built forms. Defects and maintenance that emerges from deficient design indicate that the design has not been conceded in the perception of quality. Reviewing the nature of deficient designs and resulting maintenance problems in various types of built forms revealed that housing sector is most effective of this phenomenon. The reason could be set as; housing planning, d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…Therefore, the teaching material using android-based interactive mobile learning media is feasible for students [21]. This research is based on the studies conducted by [22], which stated that mobile application needs to be interactive, attractive and easy to use for most of the targeted population because the majority of the people do not intend spending time learning the application. Furthermore, the results from the review conducted by media experts showed that three stages participate in the development process, namely initial product, main and operational field revisions.…”
Section: Percentage Of Carrying Capacity Of Android-based Interactive...mentioning
confidence: 99%
“…Therefore, the teaching material using android-based interactive mobile learning media is feasible for students [21]. This research is based on the studies conducted by [22], which stated that mobile application needs to be interactive, attractive and easy to use for most of the targeted population because the majority of the people do not intend spending time learning the application. Furthermore, the results from the review conducted by media experts showed that three stages participate in the development process, namely initial product, main and operational field revisions.…”
Section: Percentage Of Carrying Capacity Of Android-based Interactive...mentioning
confidence: 99%
“…The design of this application is made on a mobile app because the use of mobile phones is felt to be very efficient, besides that the internet has also developed data related to travel [10] [11]. Also, there are already many sectors that utilise mobile applications to facilitate users better [12]. It is evidenced by research using mobile and internet technology to provide a hybrid package recommendation system for tourism packages [13].…”
Section: Fig 1 Diving Map In Indonesiamentioning
confidence: 99%
“…Mobile apps are first tested within the development environment using emulators and later subjected to field testing. Emulators provide an inexpensive way to test applications on mobile phones to which developers may not have physical access [2]. Mobile user interface (UI) design is also essential in the development of mobile application.…”
Section: Introductionmentioning
confidence: 99%